2022
DOI: 10.30862/inornatus.v2i2.360
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity test of jatropha leaf filtrate (Jatropha curcas L.) on mortality of golden snail (Pomacea canaliculata)

Abstract: This study was an experimental study to determine the effect of the toxicity of Jatropha curcas L. leaf filtrate on the mortality of the Pomacea canaliculata (golden snail). Pomacea canaliculata as many as 240 tails aged 7 days after hatching is the object of research. A completely randomized design of 6 (treatment) and 4 (replication) was used in this study. Data was collected by observing the golden snail every hour for 24 hours. ANAVA and BNT analysis to calculate research data. Calculation of 50% mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Moreover, the rest of the aqueous extracts of other plants did not affect the snails on the first day and showed their effect on the second and third days with mortality rates ranging from 20 to 40% for plant leaf extracts such as jatropha, fireplant, jimsonweed, and neem which were (40, 30, 20, and 20%), respectively. These findings are consistent with Maruni, et al (2022) discovered that an extract from Jatropha curcas leaves were harmful to an immature golden snail and caused death within 24 h. Thapa Magar (2021) discovered that plant extracts of plant parts of neem and tirupati were more efficient in repelling and eradicating Giant African Land Snails at 5% concentration. While Sarma et al, (2019) found the Aqueous extract of the medicinal plant, Azadirachta indica (Neem) caused (98.00 ± 0.29) mortality at 6% concentration after 72 h of an adult insect, banana beetle with an LC50 rate was 3.95 mg/L, by direct spray way under the laboratory.…”
Section: Resultssupporting
confidence: 79%
“…Moreover, the rest of the aqueous extracts of other plants did not affect the snails on the first day and showed their effect on the second and third days with mortality rates ranging from 20 to 40% for plant leaf extracts such as jatropha, fireplant, jimsonweed, and neem which were (40, 30, 20, and 20%), respectively. These findings are consistent with Maruni, et al (2022) discovered that an extract from Jatropha curcas leaves were harmful to an immature golden snail and caused death within 24 h. Thapa Magar (2021) discovered that plant extracts of plant parts of neem and tirupati were more efficient in repelling and eradicating Giant African Land Snails at 5% concentration. While Sarma et al, (2019) found the Aqueous extract of the medicinal plant, Azadirachta indica (Neem) caused (98.00 ± 0.29) mortality at 6% concentration after 72 h of an adult insect, banana beetle with an LC50 rate was 3.95 mg/L, by direct spray way under the laboratory.…”
Section: Resultssupporting
confidence: 79%
“…Because of its flexibility, mobility, and high reproductive capacity, the golden snail (Pomacea canaliculata) is one of the rice pests that is challenging to manage. The reason the golden snail is referred to as a nuisance is that it consumes 10-day-old rice plants in rice fields, and the eggs that the golden snail lays cause the rice plants to perish (Maruni et al, 2022).…”
Section: Introductionmentioning
confidence: 99%